SOME RELATIONSHIPS ASSOCIATED WITH THE BROWN FIBRE INDUSTRY OF SRI LANKA - S. B. Ratnayake (International Coconut Community, 1995)
Export onented brownfibre industry of Sn Lanka has been sustained during the last two decades with periodic fluctuations in the annual voluntes, showing a nett decline towards later years. The level of export volume in the past years show a strong correlation with the number of drought days in the coconut area during the particular year. The increased exportscan be expected to result in withdrawal of husk available for application in moisture conservation of the cultivated lands. Yhe effect would be aggravated by most exports being effected in the drought years. High incidence offibre expons, as it seenu when viewed against the annual crop pattern, lead to a drop in the harvests of thefollowing years. Means of avoiding the damage, thus caused while maintaining a satisfactory level of exports, maybe the primary factor to be concerned with, in planning future development programmes.